2019
DOI: 10.1002/humu.23932
|View full text |Cite
|
Sign up to set email alerts
|

A DM1 family with interruptions associated with atypical symptoms and late onset but not with a milder phenotype

Abstract: Carriage of interruptions in CTG repeats of the myotonic dystrophy protein kinase gene has been associated with a broad spectrum of myotonic dystrophy type 1 (DM1) phenotypes, mostly mild. However, the data available on interrupted DM1 patients and their phenotype are scarce. We studied 49 Spanish DM1 patients, whose clinical phenotype was evaluated in depth. Blood DNA was obtained and analyzed through triplet-primed polymerase chain reaction (PCR), long PCR-Southern blot, small pool PCR, AciI digestion, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 26 publications
(81 reference statements)
3
22
0
Order By: Relevance
“…Supporting this, a correlation between methylation levels and age of onset has been reported previously [4,19]. Repeat interruptions have been linked to both higher downstream methylation levels [4,20] and later disease onset [16,17], and it is thus likely that this effect would have to be accounted for if an association between methylation levels and age of onset is to be made. The results of our longitudinal methylation study indicated that the methylation levels do not change with age, which contradicts the idea that age is a modifier of DMPK methylation levels.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Supporting this, a correlation between methylation levels and age of onset has been reported previously [4,19]. Repeat interruptions have been linked to both higher downstream methylation levels [4,20] and later disease onset [16,17], and it is thus likely that this effect would have to be accounted for if an association between methylation levels and age of onset is to be made. The results of our longitudinal methylation study indicated that the methylation levels do not change with age, which contradicts the idea that age is a modifier of DMPK methylation levels.…”
Section: Discussionmentioning
confidence: 56%
“…Research over the last decade has shown that the variability in clinical phenotype and age of onset can be correlated to sequence interruptions in the CTG repeat [13,[16][17][18], as well as DNA methylation of the area surrounding the CTG repeat [19,20]. The hypermethylation of the DM1 locus was, at first, thought to only be present in patients with congenital onset DM1 (CDM1) [21]; however, studies have shown hypermethylation to also be present in patients with non-congenital DM1 [4,19,22] and particularly in patients with repeat interruptions [4,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a DM1 family was found to have ‘CCG’ interruptions within the ‘CTG’ STR expansion in DMPK resulting in atypical traits such as severe axial and proximal weakness and late onset of symptoms [ 9 ].…”
Section: General Characteristics Of Repeat Expansion Disordersmentioning
confidence: 99%
“…With traditional TP-PCR careful examination of the electropherograms from published reports of DM1 cases with interrupted CTG repeats show that the TP-PCR reaction does not fail, but proceeds with interruptions to the typical sawtooth pattern seen from uninterrupted CTG repeats. 11, 29, 31, 32 Indeed, TP-PCR has been used in search of interrupted repeats. 33 As we have shown by melt curve reconstruction, since our application of MCA uses the full spectrum of TP-PCR products, it is robust at detecting differences in the relative proportion of fragment lengths.…”
Section: Discussionmentioning
confidence: 99%